2005
DOI: 10.1002/cncr.21539
|View full text |Cite
|
Sign up to set email alerts
|

A population‐based description of glioblastoma multiforme in Los Angeles County, 1974–1999

Abstract: BACKGROUND There have been reports that the incidence rates of brain tumors have increased over the past few decades, but most have considered all brain tumors together. The authors analyzed the pattern of glioblastoma multiforme (GBM) occurrence in Los Angeles County, California to shed light on the incidence and descriptive epidemiology of this type of brain tumor. METHODS Data were obtained from the Los Angeles County Cancer Surveillance Program. Incidence rates were analyzed by gender, race, age at diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
4
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(137 citation statements)
references
References 27 publications
8
122
4
3
Order By: Relevance
“…Several published works showed that brain tumors are related to Socio-Economical Status (SES) and people of higher SES are at a higher risk for developing brain tumors (Demers, 1991;Navas-Acién et al, 2002;Chakrabarti et al, 2005). Mobile phones penetration in the Israeli society was very rapid and reached 100% of the adult population in 6 years since its introduction to the general public.…”
Section: Mobile Phone Penetrationmentioning
confidence: 99%
“…Several published works showed that brain tumors are related to Socio-Economical Status (SES) and people of higher SES are at a higher risk for developing brain tumors (Demers, 1991;Navas-Acién et al, 2002;Chakrabarti et al, 2005). Mobile phones penetration in the Israeli society was very rapid and reached 100% of the adult population in 6 years since its introduction to the general public.…”
Section: Mobile Phone Penetrationmentioning
confidence: 99%
“…4,20,21,40,46 As the incidence of GBM has been rising in elderly patients while this population group rapidly expands, it is increasingly important to identify prognostic factors and effective therapeutic strategies for improving survival in elderly patients. 5,18 Current therapy for GBM consists of maximal safe resection followed by radiotherapy (RT) and concomitant temozolomide (TMZ). However, the optimum treatment strategy for elderly patients is unclear because of the available data, which are limited for several reasons.…”
mentioning
confidence: 99%
“…Additionally, the incidence of GBM in older adults has been increasing [4][5][6]. Optimal management of older patients with GBM remains uncertain because their survival tends to be short and they are at greater risk for surgery, radiation treatment and chemotherapy complications owing to their comorbidities.…”
Section: Elderlymentioning
confidence: 99%